Molecular Biology of the GENE - Watson, James D. (New Delhi Affiliated East West Press, 2024)
The new Multi-Colour edition of the classic book from Dr James Watson, nobel laureate , on the 71 st anniversary of the discovery of the structure of the DNA in 1953. The field of molecular biology as we understand today was born out of the discovery of the DNA Strucure.
Includes Index
Keywords: Molecular biology; Genes; Molecular Genetics; DNA; Genomics